THE 2024 LOCAL ELECTIONS IN THE REPUBLIC OF SERBIA – POLITICAL DYNAMICS AND CONSEQUENCES - Matić, Petar; Mijatovic, Marko (Serbian political thought, 2024)
In this paper, we will analyze the political dynamics of the last cycle of local elections in Serbia. We will refer to the existing institutional framework as well as the reforms in this field of electoral law that preceded the elections themselves. In this sense, in the first part, the institutional paradigm will be applied in order to investigate the institutional context. The second section analyzes the broader socio-political context that influenced turnout and election results. In the third section, attention is paid to electoral actors, either individual parties or their coalitions. Minority parties that take part in the election game under special conditions through forms of positive discrimination are dealt with. The fourth section is devoted to the formation of local authorities, while a separate part is related to groups of citizens as separate political actors in local areas. The conclusion refers to the key findings of this research.Forming a certain whole with the local elections held in the city of Belgrade and another 65 municipalities, cities and urban municipalities in central Serbia, on December 17, 2023, they showed a picture of the political scene of Serbia, its dynamics, actors at the national and local level, their strategies political struggles and, finally, electoral preferences citizens related to the political game in local political arenas.These elections were a test of sorts since they were held separately from the parliamentary elections at the end of 2023. They also provide an excellent basis for analyzing the political consequences in case of their separation in relation to national elections, given that for half a year in a number of cities and municipalities, local elections were held simultaneously with national ones.